ISSUES OF PROFESSIONAL TRAINING CIVIL AND MILITARY AVIATION PERSONNEL - Ладогубець, Н. В.; Марченко, О. Г. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
Comparative analysis of the content of professional activities and training of flight personnel of civil and military aviation is made in the article. It is proposed to use the training of pilots for light aircraft as a resource for further re-training of military pilots